STUDY OF DEMOGRAPHIC ANALYSIS, CLINICAL CHARACTERISTICS, DIAGNOSIS, MANAGEMENT AND COMPLICATIONS IN COVID-19 PATIENTS - PAVAN KUMAR M; REVATHI G; SUPRAJA K, SECHANA K (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: To study the demographic analysis, clinical characteristics, diagnosis, and management in covid-19 patients. To assess the complications in covid-19 patients. Methods: A retrospective observational single centered study is carried out to study the demographic analysis, clinical characteristics, diagnosis, management, and complications in covid-19 patients. Results: Among 100 covid-19 patients 58% were male and 42% were female. Percentages of age group between 60-70 years (27%), 50-60 (20%), 40-50 (16%), 70-80 (16%), 30-40 (8%), 20-30 (5%), 80-90 (4%), and 10-20 (4%). Co-morbidities were diabetes (44%), hypertension (28%), CAD (21%), thyroid (19%), COPD (12%), anemia (8%), and renal impairment (4%). Signs and symptoms were fever (88%), cough (80%), SOB (72%), fatigue (68%), myalgia (60%), loss of appetite (52%), cold (24%), loss of smell and taste (20%), diarrhea and vomiting (12%). (97%) of the patients had two or more symptoms. Diagnostic test include RT-PCR (100%), HRCT (100%), O2 saturation (99%), D-dimer (65%), c-reactive (60%), Procalcitonin (60%), and also LDH, IL-6,PT, INR, ferritin, CBP, WBC. Treatment includes antiviral (100%), antibiotics (100%), corticosteroids (73%), immunosuppressant (54%), and antihypertensive, antidiabetic, Antiplatelets, bronchodilators, vitamins, and mineral supplements. Conclusion: Covid-19 infects the males more and average ages of 65 years are at risk. Hypertension and diabetes were most common co-morbid condition. Fever and cough are major followed by weakness sob and cold. RT- PCR and HRCT are accurate tool to detect covid-19. Although standard treatment is not yet available antibiotics and antiviral are used followed by corticosteroids. Majority of the patients have mild and moderate injection and with the lowest death rate. Older age and co-morbid conditions are major risk factors.